Can family-support policies help explain differences in working hours across countries? - Sila, Urban (London, 2009)
"It has been suggested in the literature that taxes and subsidies play an important role in explaining the differences in working hours across countries. In this paper I test whether public programmes for family support play a role in explaining this variation. I analyse two types of policies: childcare subsidies and family cash benefits. I distinguish between people with children and people without children. Childcare subsidies should increase working hours in the economy and these effects should differ between people with children and people without children. Public support to families is also expected to decrease the amount of time people spend in childcare at home. I test this using household data for a set of European countries and the US. Empirical analysis, however, does not support the family-policy explanation. The effects of the policies on working hours are weak and insignificant. In regressions with time spent caring for children as a dependent variable, the estimates of the effects contradict the predictions of the theory. Furthermore, I don’t find evidence for the expected differences in effects between parents and nonparents. I conclude that family policies are not helpful in explaining the variation in working hours across countries."